WUJUD RASA SYUKUR SEBAGAI KELUARGA PETANI DALAM VISUAL KARYA SENI GRAFIS - Prastyo, Irfan Dwi; Zarkasi, Much Sofwan (Brikolase : Jurnal Kajian Teori, Praktik dan Wacana Seni Budaya Rupa, 2019)
The lesson from life as farm family inspire personal life to patient, work hard, simple, sharing and help each other in daily life and also contribute to self-maturing. Purpose of create this printmaking artwork is creating printmaking artwork which take form thankfulness as farm family and also explain about concept, process creating and visual aesthetic result from printmaking artwork. Form of thankfulness as farm family is visualized in printmaking artwork with relief print technic use hardboardcut on paper. These creating printmaking artworks give more insight from empirical experience in creating printmaking artwork and also deepen about concept form thankfulness as farm family